PENGARUH BEBAN PROMOSI TERHADAP DANA YANG DIHIMPUN PIHAK KETIGA PADA PT BANK MANDIRI PERSERO TBK, JAKARTA - Rina Apriliani; Wulan Diantini (POLITEKNIK LP3I JAKARTA, 2021)
Third party funds are funds sourced from the public, namely in the form of savings, current accounts or time deposits. Many factors can increase third party funds, one of which is promotion costs. Promotional expenses are costs incurred by banks to carry out promotions in order to increase the quantity of sales. This study aims to produce information in the form of a more in-depth explanation of the effect of promotional expenses on third party funds and obtain results from processed data on how much influence the promotional expenses have on third party funds. The research method used a quantitative descriptive method, namely some researchers who emphasize numerical data that is processed in statistical methods. Based on calculations using a simple linear regression equation between X and Y is Y = 380716222,908 + 480,123X…e the coefficient of determination is R Square = 0,517 or 51.7% of third party funds, while the remaining 48.3% is influenced by the variables not researched. The relationship test, namely the correlation analysis of R = 0.719 and the hypothesis testing (t) the promotion expense variable tcount 5.668 > ttable 2.04227, it can be said that the relationship between the promotional expense variable and third party funds is strong.Key words: Banks, Promotional Expenses and Investor Funds